Type-I Interferons in Alzheimer's Disease and Other Tauopathies - Sanford, Sophie A. I.; McEwan, William A. (Frontiers in Cellular Neuroscience, 2022)
The detection of pathogen-associated molecular patterns can elicit the production of type-I interferons (IFNs), soluble cytokines that induce a transcriptional state inhibitory to viral replication. Signatures of type-I IFN-driven gene expression, and type-I IFNs themselves, are observed in the central nervous system during neurodegenerative diseases including Alzheimer’s disease and other tauopathies, the umbrella term for diseases that feature aggregation of the cytosolic protein tau. The contribution of the type-I IFN response to pathological progression of these diseases, however, is not well understood. The wholesale transcriptional changes that ensue from type-I IFN production can both promote protective effects and lead to damage dependent on the context and duration of the response. The type-I IFN system therefore represents a signalling pathway with a potential disease-modifying role in the progression of neurodegenerative disease. In this review we summarise the evidence for a type-I IFN signature in AD and other tauopathies and examine the role of aggregated proteins as inflammatory stimuli. We explore both the protective role of IFN against protein pathologies as well as their downstream toxic consequences, which include the exacerbation of protein pathology as a potentially destructive feed-forward loop. Given the involvement of type-I IFNs in other neurogenerative diseases, we draw comparisons with other categories of homotypic protein aggregation. Understanding how type-I IFN influences progression of AD and other tauopathies may yield important insight to neurodegeneration and identify new targets in an area currently lacking disease-modifying therapies.